Re-Creating an Aboriginal Earth Oven with Clayey Heating Elements: Experimental Archaeology and Paleodietary Implications - Maurizio Campanelli (EXARC, 2018)
Earth ovens may relate to different ancestral cooking techniques, serving specific needs and functions. In eastern and south-eastern Australia, they were a significant element of a thriving pre-colonial Aboriginal culture. However, today it is extremely rare to find such structures well preserved. Based on archaeological and historical records, we re-created an earth oven with clayey heating elements in Jadawadjali Country, central western Victoria, and cooked a culturally significant Aboriginal staple food: the yam daisy or murnong. The aims of the experiment were to explore the cooking process and investigate the nutritional implications of using this earthen structure for cooking these tuberous roots. Nutritional analyses of fresh and cooked samples of Microseris scapigera (used in place of the traditional M. walteri), reveal that the cooking process does not increase the chemical potential energy, but softens and sweetens the solid matter, perhaps providing a desirable and warm baby food. Detailed carbohydrate analysis revealed that the M. scapigera is a good source of prebiotic inulin-type fructans (2.71 g/100 g wet wt).